Pelatihan Manasik sebagai Syarat Haji Perspektif Ulama Aceh - Nasrullah Nasrullah; Abdullah Abdullah; Chalidin Chalidin (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2019)
The word manasik in several Qur’anic verses and hadith shows the importance of the perfection of the Hajj. Classical Muslim scholars do not discuss specifically about manasik, but nowadays the manasik (hajj rituals) training for prospective pilgrims has been coordinated by government. This requires new ijtihad for the legality of Hajj ritual training, especially among Acehnese scholars. This research examines how the position of manasik is within the scope of the Hajj rules; how the Aceh Ulamas view and consider the manasik training as a requirement of Hajj. This study uses a qualitative method. The results of the study indicate that the position of manasik training within the scope of the Hajj rule is as an observance and knowledge of the procedures for performing the Hajj. Learning Hajj rituals includes an observance and it is obligatory for people who do not understand it such as conditions, requirements and things that are not permitted during Hajj. Acehnese Ulama are of the view that the Hajj manasik training cannot be used as a requirement of Hajj, but there are also those who argue that in the present conditions the manasik training can be used as a requirement of the Hajj and it can even become mandatory. The existence of differences of opinion in carrying out ijtihad is caused by legal basis considerations and the logic used.